"No pain, no gain": The impact of autonomous sensory meridian response on pain perception. (August 2022) - Janik McErlean, Agnieszka B.; Ellis, Lucy; Walsh, Joseph
Autonomous sensory meridian response (ASMR) is a phenomenon characterised by a static-like tingling sensation spreading from the scalp and neck to the periphery in response to a variety of audio, visual, and tactile triggers resulting in a highly relaxed state and boosted positive affect. The limited literature on this phenomenon points to a potential of ASMR to alleviate pain. Emerging evidence also suggests that ASMR may be linked to increased sensory sensitivity more broadly. This study aimed to objectively address these claims by administering an algometer (measure of pain tolerance), and a visual analog scale (VAS) (measure of subjective pain sensitivity) to ASMR experiencers and controls at baseline, following an ASMR video, and a control video. Findings indicate that ASMR experiencers have a higher pain sensitivity than controls; however, there was no difference between the two groups in terms of pain tolerance. In addition, any potential analgesic properties associated with experiencing ASMR may reflect protective properties of ASMR buffering against the increased pain sensitivity among ASMR experiencers relative to controls.